Cybersecurity maturity framework for international airports in Malaysia: a systematic literature review (SLR) / Suzaliana Samuri ... [et al.] - Samuri, Suzaliana; Abdul Khir, Mohd Fared; Mohd Amin, Zahari; Mohammad, Mohammad Fakhrul Nizam (Faculty of Information Management, 2023)
This paper presents an approach for conducting a systematic literature review on the Cybersecurity Maturity Framework (CSMF) specific to international airports in Malaysia. The systematic review comprises three stages: identification, screening, and included. Rigorous screening of results was accomplished by applying predetermined inclusion and exclusion criteria. This systematic literature review comprehensively explains the prevalent frameworks, models, and standards for evaluating cybersecurity maturity. The insights derived from this review substantially informed the development of a cybersecurity maturity framework tailored to international airports in Malaysia.